2009
DOI: 10.1242/jeb.020990
|View full text |Cite
|
Sign up to set email alerts
|

Energetic costs of detoxification systems in herbivores feeding on chemically defended host plants: a correlational study in the grain aphid,Sitobion avenae

Abstract: SUMMARYHerbivorous insects have developed mechanisms to cope with plant barriers, including enzymatic systems to detoxify plant allelochemicals. Detoxification systems may be induced when insects are feeding on plants with increasing levels of allelochemicals. Increases in enzymatic activity have been related to energetic costs, and therefore less energy may be allocated to fitness-related traits. In this study, we explored the induction and energetic costs of detoxifying hydroxamic acids (Hx; a wheat alleloch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 45 publications
5
49
1
Order By: Relevance
“…To estimate SMR in eggs, we followed the system described by Castañeda et al (2009) for measuring very small arthropods (less than 0.1 g). In brief, each egg was placed in a 2-mL glass syringe, which was sealed, filled with CO 2 -free air to a volume of 1.5 mL, and placed in a dark climatic chamber at 20Њ ‫ע‬ .…”
Section: Respirometry and Dehydration Rate: Eggsmentioning
confidence: 99%
“…To estimate SMR in eggs, we followed the system described by Castañeda et al (2009) for measuring very small arthropods (less than 0.1 g). In brief, each egg was placed in a 2-mL glass syringe, which was sealed, filled with CO 2 -free air to a volume of 1.5 mL, and placed in a dark climatic chamber at 20Њ ‫ע‬ .…”
Section: Respirometry and Dehydration Rate: Eggsmentioning
confidence: 99%
“…There are no works on succivorous insects of C. arabica. Other studies examining the relationship between insect Þtness and plant chemistry also have reported varying results (Castañ eda et al 2009, Castañ eda et al 2010. Nevertheless, these studies generally found a positive relationship between insect performance and a plantÕs nitrogen content, with a negative relationship for secondary compounds (e.g., total phenols, tannins, and monoterpenes).…”
mentioning
confidence: 99%
“…secondary compounds from plants or insecticides); including P450s, GSTs, esterases and oxidoreductases383940414243. Some of these enzymes are known to be involved in the detoxification of mycotoxins20.…”
Section: Discussionmentioning
confidence: 99%